Follicular microenvironment modulation in androgenetic alopecia: preliminary clinical observations with autologous adipose-derived micrografts and polynucleotides - Amore, Antonio Luca; Di Pasquale, Basso; Gennai, Alessandro (Aesthetic Medicine, 2026)
Background: Androgenetic alopecia (AGA) is a chronic multifactorial condition characterized by progressive follicular miniaturization. Beyond androgen-mediated mechanisms, increasing evidence highlights the role of perifollicular microinflammation, vascular alterations, and stromal remodeling in disease progression. Targeting the follicular microenvironment may therefore represent a complementary therapeutic strategy.Objective: To evaluate the clinical and trichoscopic outcomes of a combined regenerative protocol based on autologous adipose-derived micrografting and intradermal polynucleotide administration in patients with AGA.Methods: Four patients (two males and two females) with clinically and trichoscopically confirmed AGA were included. Disease severity was classified using the Norwood–Hamilton scale (male patients) and the Ludwig scale (female patients). All patients underwent a single session of autologous adipose-derived micrografting performed using a mechanical processing system (SEFFIHAIR®, SEFFILINE S.r.l., Bologna, Italy), combined with intradermal injections of polynucleotides (Nucleofill® Medium, Promoitalia S.r.l., Milan, Italy), followed by five additional polynucleotide sessions at two-week intervals. Clinical and trichoscopic assessments were conducted at baseline and at 4 months.Results: Patients with early to intermediate AGA demonstrated reduced hair shaft diameter variability and improved apparent density. The advanced-stage patient showed mild qualitative improvement without significant density increase. No adverse events were observed.Conclusion: These preliminary findings suggest that modulation of the follicular microenvironment through combined regenerative strategies may represent a potential adjunctive approach, particularly in early-stage AGA.